What is 9/6 minus 6/2?
Looking for the result of 9/6 - 6/2? Follow this step-by-step guide to understand how to subtract these two fractions.
How to subtract 9/6 by 6/2?
- Multiply the numerator of the first term, with the denominator of the second term: 9 × 2 = 18
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 6 = 36
- Subtract both of these results together to form the new numerator: 18 − 36 = -18
- Multiply both denominators together to form the new denominator: 6 × 2 = 12
- Combine the results to get the new fraction: -18/12
- Simplify the fraction (-18/12) by dividing both the numerator and the denominator by their GCD (6):
- -18/6 = -3
- 12/6 = 2
- This gives: -3/2.
The result of subtracting 9/6 and 6/2 is : -3/2 (or -1.5 in its decimal form)